Prosperity for the Poor: Religion, Poverty and Development in Sub-Saharan Africa - Appau, Samuelson; Mabefam, Matthew Gmalifo (Moving from the Millennium to the Sustainable Development Goals: Lessons and Recommendations, 2020)
In this chapter, the authors present a much-needed discussion on the role of religion in the development process in Sub-Saharan Africa. The authors invoke the case of the very popular Pentecostal prosperity gospel doctrine, a “religious policy” on poverty alleviation that promises material wealth and health to all believers through faith and monetary offerings to God (church). The authors examine how this doctrine is shaping local imaginations of poverty, and the moral agency of pursuing wealth in the market economy, as well as the ethics and apologetics of the doctrine’s material costs. The chapter therefore presents a useful invitation to development stakeholders and researchers to take religion more seriously in the conversation on development and poverty alleviation in Africa.
paid